2016
DOI: 10.1161/circinterventions.115.003425
|View full text |Cite
|
Sign up to set email alerts
|

Early Recovery of Left Ventricular Systolic Function After CoreValve Transcatheter Aortic Valve Replacement

Abstract: Background-Approximately one third of patients with symptomatic aortic stenosis have reduced left ventricular ejection fraction (LVEF) before transcatheter aortic valve replacement. The incidence, predictors, and significance of early LVEF recovery after CoreValve transcatheter aortic valve replacement have not been described. Methods and Results-We studied 156 patients from the CoreValve Extreme and High-Risk trials with LVEF ≤40% at baseline who had 30-day LVEF data. All patients underwent core laboratory ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 32 publications
(55 reference statements)
6
46
2
Order By: Relevance
“…We observed a signifi cant increase in the left ventricular ejection fraction and a signifi cant decrease in the left ventricular enddiastolic diameter after the procedure. Other authors presented similar results (24,25) and our fi ndings concur with the PARTNER trial fi nding that included patients with left ventricular dysfunction between 40-50 % (1, 2).…”
Section: Discussionsupporting
confidence: 90%
“…We observed a signifi cant increase in the left ventricular ejection fraction and a signifi cant decrease in the left ventricular enddiastolic diameter after the procedure. Other authors presented similar results (24,25) and our fi ndings concur with the PARTNER trial fi nding that included patients with left ventricular dysfunction between 40-50 % (1, 2).…”
Section: Discussionsupporting
confidence: 90%
“…While both kinds of valve showed similar changes in transaortic gradients and AVA after the procedure, the group receiving the self-expanding valve achieved a statistically significant improvement in LV systolic function as assessed by the Simpson biplane method, which could in turn explain the difference in GLS improvement. Although previous studies have also shown an early improvement in LV systolic function with the self-expanding valve [20], the reason for this difference in early LV mechanic behaviour remains unclear and should be clarified in further studies.…”
Section: Vanesa Cristina Lozano Granero Et Al Left Ventricular Mechmentioning
confidence: 85%
“…About a third of patients undergoing TAVR present with depressed LV ejection fraction (LVEF). In 156 patients in the Core Valve Extreme and High Risk trials, early LVEF recovery (>10% improvement in LVEF by 30 days) occurred in 62% of patients, and was associated with better 1‐year survival than the no‐early recovery group (12% vs 24%; P = 0.07). Absence of previous myocardial infarction and baseline mean gradient ≥40 mm Hg were identified as predictors of early LVEF recovery.…”
Section: Introductionmentioning
confidence: 99%